IEEE 802.15.4 and zigBee as enabling technologies for low-power wireless systems with quality-of-service constraints - Tennina, Stefano; Daidone, Roberta; Alves, Mario; Jurčík, Petr (Springerbriefs in electrical and computer engineering, 2013)
This book outlines the most important characteristics of IEEE 802.15.4 and ZigBee and how they can be used to engineer Wireless Sensor Network (WSN) systems and applications, with a particular focus on Quality-of-Service (QoS) aspects. It starts by providing a snapshot of the most relevant features of these two protocols, identifying some gaps in the standard specifications. Then it describes several state-of-the-art open-source implementations, models and tools that have been designed by the authors and have been widely used by the international community. The book also outlines the fundamental performance limits of IEEE 802.15.4/ZigBee networks, based on well-sustained analytical, simulation and experimental models, including how to dimension such networks to optimize delay/energy trade-offs.